2007
DOI: 10.1002/lapl.200710097
|View full text |Cite
|
Sign up to set email alerts
|

High-power continuous wave and passively Q-switched laser operations of a Nd:GGG crystal

Abstract: Abstract:We report on the continuous wave (CW) and passive Q-switching performance of a high-power diode-pumped Nd:GGG laser. A CW output power of 7.20 W was obtained under an absorbed pump power of 14.97 W, which gives a slop efficiency of 52.7%. With a Cr 4+ doped yttrium aluminum garnet crystal as the saturable absorber, the shortest passively Qswitched pulse width, largest pulse energy, and highest peak power achieved were 7.7 ns, 126.25 µJ, and 15.5 kW, respectively.Intensity, a.u. Time, µs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(37 citation statements)
references
References 16 publications
0
37
0
Order By: Relevance
“…The threshold pump powers were measured to be 0.07 W, 0.16 W, 0.36 W, 0.64 W, 0.90 W, and 1.29 W, respectively corresponding to the output coupler of 1.7%, 5%, 10%, 15%, 20%, and 27%. The higher power obtained in our experiment should be contributed to the fact that the mode volume was larger than that of reference [12]. Fig.…”
Section: Resultsmentioning
confidence: 65%
“…The threshold pump powers were measured to be 0.07 W, 0.16 W, 0.36 W, 0.64 W, 0.90 W, and 1.29 W, respectively corresponding to the output coupler of 1.7%, 5%, 10%, 15%, 20%, and 27%. The higher power obtained in our experiment should be contributed to the fact that the mode volume was larger than that of reference [12]. Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Nd:GGG also presents a number of very favorable properties, such as (i) a large thermal conductivity and a large thermal capacity, which is important in case of applications requiring high power laser levels [26][27][28], (ii) relatively broad absorption and emission lines while presenting relatively large absorption and emission cross sections [29], which is important for diode pumping and low threshold laser action. In fact, during the past decade, Nd:GGG has been studied and successfully operated around 1.06 mm as well as 1.33 mm either CW at medium high power levels [30,31] or pulsed in the Q-switched [19,32] and mode-locked [20] laser regimes. Some new infrared laser emissions were also reported around 1.1 mm [33], as well as the generation of green and blue laser wavelengths around 552 nm [34] and 468 nm [35] via intra-cavity nonlinear frequency doubling.…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, we obtained a maximum CW output power of 13.2 W, L.J. Qin et al have reported the CW and passive Q-switching performance of a high-power diode-pumped Nd:GGG laser [9]. But there was no any report about the acousto-optic performance of the Nd:GGG laser.…”
Section: Introductionmentioning
confidence: 94%